Ambulatory blood pressure monitoring for the management of hypertension. Issue 9 (5th May 2022) - Cheng, Yibang; Li, Yan; Wang, Jiguang
Abstract : Abstract: Ambulatory blood pressure monitoring (ABPM) has become indispensable in the current management of hypertension. ABPM is particularly useful in the accurate diagnosis of hypertension. Its diagnostic thresholds had been recently established based on hard clinical outcomes. Cross-classification of patients according to office and ambulatory blood pressure identifies white-coat, masked, and sustained hypertension. ABPM is also useful in cardiovascular (CV) risk assessment. It provides information on daytime and nighttime blood pressure and circadian rhythm, particularly nighttime blood pressure dipping. Nighttime blood pressure is predictive of CV risk independent of office and daytime blood pressure. Isolated nocturnal hypertension is a special form of masked hypertension, with normal daytime but elevated nocturnal blood pressure. It also helps in the evaluation of blood pressure fluctuation and variation, such as morning blood pressure surge and reading-to-reading blood pressure variability. ABPM may derive several other indexes, such as ambulatory blood pressure index and salt sensitivity index, which may be useful in CV evaluations.